Pengaruh Kualitas Pelayanan Fiskus, Pemahaman Perpajakan dan Insentif Pajak terhadap Kepatuhan Wajib Pajak - Lafau, Aryanti; Widiyati, Dian (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2024)
This research aims to determine the influence of tax service quality, understanding of taxation and tax incentives on taxpayer compliance. This type of research is quantitative research using a random method (Random Sampling) in collecting data samples and the type of data used is primary data. The population of this research is Taxpayers registered at KPP Pratama Serpong. The number of samples distributed was 55 respondents. The data analysis techniques used are descriptive statistics, data quality testing, classical assumption testing and hypothesis testing. The research results show that the results of the F statistical test show that simultaneously the value of Fcount > Ftable (11.531 > 2.79), so it can be concluded that the Quality of Fiscus Services, Understanding of Taxation and Tax Incentives simultaneously have a significant effect on Taxpayer Compliance. The quality of Fiscus Services in particular has no effect on Taxpayer Compliance. Understanding Taxation partially influences Taxpayer Compliance. Partial tax incentives have no effect on Taxpayer Compliance.